Process‐dependent residual trapping of CO2 in sandstone. Issue 8 (24th April 2014) - Zuo, Lin; Benson, Sally M.
Abstract This paper demonstrates that the nature and extent of residual CO2 trapping depend on the process by which the CO2 phase is introduced into the rock. We compare residual trapping of CO2 in Berea Sandstone by imbibing water into a core containing either exsolved CO2 or CO2 introduced by drainage. X‐ray computed tomography measurements are used to map the spatial distribution of CO2 preimbibition and postimbibition. Unlike during drainage where the CO2 distribution is strongly influenced by the heterogeneity of the rock, the distribution of exsolved CO2 is comparatively uniform. Postimbibition, the CO2 distribution retained the essential features for both the exsolved and drainage cases, but twice as much residual trapping is observed for exsolved CO2 even with similar preimbibition gas saturations. Residually trapped exsolved gas also disproportionately reduced water relative permeability. Development of process‐dependent parameterization will help better manage subsurface flow processes and unlock benefits from gas exsolution.